OPTIMASI PRODUK KOPI BATUAH DENGAN HERBAL TRADISIONAL DI KELURAHAN KEMUNING KECAMATAN BANJARBARU SELATAN - Didik Rio Pambudi; Muhammad Reza Fahlevi; Fitriyanti Fitriyanti; Karunika Ika Astuti; Azmi Yuniarti (Jurnal Bakti untuk Negeri, 2022)
Optimizing coffee products with herbs is part of applying science to social life. Coffee products with herbs aim to maintain endurance during the pandemic and help improve the economic level of the community. The implementation method is by conducting socialization, development training and education for a massive and effective marketing strategy. This activity targets MSMEs in the Kemuning village which was attended by 20 groups of participants. Participants benefit from this training because they can do promotions with better and more targeted photos of product results so that they can attract more buyers' interest. The conclusion of this activity is the need for an active role from academics to channel their expertise, knowledge and ideas to help the community survive and develop, especially in the current pandemic era.